1995
DOI: 10.1088/0953-8984/7/41/001
|View full text |Cite
|
Sign up to set email alerts
|

Formation and characterization of silicon nanoparticles-threads, tubules and possibly silicon fullerene-like structures

Abstract: We report the formation of nanoparticles of silicon (thread-like nanostructures of diameter approximately=2 nm and length a few microns, as if nanocrystals are linked together along curly tubules), the occurrence of a tubule-like configuration, whiskers and a new phase with large periodicity, a=14.25 AA, f.c.c. silicon, when evaporated under helium ambience (100 Torr) and characterized through transmission electron microscopic techniques, revealed several curious characteristics as mentioned above. We have sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
2
12
0
1
Order By: Relevance
“…The diffraction patterns showed presence of crystalline phases of Si possessing large periodicities ͑e.g., aϭ14.25 Å). Extensive electron microscopic explorations of the sample revealed that, in addition to the crystalline fcc (aϭ14.25 Å) phase, which has already been reported by us, 16 another structural variant corresponding to quasicrystalline phase exhibiting tenfold symmetry was also present. The ten-fold patterns shown in Figs.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The diffraction patterns showed presence of crystalline phases of Si possessing large periodicities ͑e.g., aϭ14.25 Å). Extensive electron microscopic explorations of the sample revealed that, in addition to the crystalline fcc (aϭ14.25 Å) phase, which has already been reported by us, 16 another structural variant corresponding to quasicrystalline phase exhibiting tenfold symmetry was also present. The ten-fold patterns shown in Figs.…”
Section: Resultssupporting
confidence: 71%
“…The as-deposited films, as described elsewhere, 16 had typical thread-like microstructures resulting from nanocrystals linked together. The details of these features have already been described earlier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sans chercher en fait à élaborer une structure de type clathrate, Kamalakaram et al [188] ont obtenu par évaporation thermique du silicium sous une pression de 100 Torr d'hélium des nanoparticules en forme de fils et de tubules, ainsi que quelques microcristaux d'une nouvelle phase cubique à faces centrées ayant un paramètre de maille de 1425 pm et une structure constituée de clusters Si 28 . Cette étonnante co€ ıncidence avec le clathrate Si 136 , dont ils semblent ignorer l'existence, n'a pas été relevée par les auteurs concernés qui n'ont pas donné suite à cette intéressante expéri-ence.…”
Section: Comportement Des Clathrates Sous Hautes Pressionsunclassified
“…Nevertheless, the detailed structures, stabilities, and properties of these Si heterofullerenes are still far from being well understood, although some theoretical work has been done, even in fully substituted Si 60 [53] and Si 28 [54], which experimentally have not been observed so far. We hereby undertake a theoretical study on two selected heterofullerenes C 2n−m Si m (with 2n = 28, 60; m = 1, 2, 3).…”
Section: Introductionmentioning
confidence: 99%